2022
DOI: 10.1177/1098612x221135105
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral lysis of aortic saddle thrombus with early tissue plasminogen activator (BLASTT): a prospective, randomized, placebo-controlled study in feline acute aortic thromboembolism

Abstract: Objectives The aim of this study was to investigate the impact of tissue plasminogen activator (TPA) on the treatment of feline aortic thromboembolism (FATE). Methods Cats diagnosed with FATE involving ⩾2 limbs were enrolled in a prospective, multicenter, double-blinded, randomized, placebo-controlled study within 6 h of an event. Diagnosis was made by clinical findings and one confirmatory criterion. Cats received placebo or TPA (1 mg/kg/h with the first 10% by bolus). All cats received pain control and throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(46 citation statements)
references
References 35 publications
8
32
0
6
Order By: Relevance
“…Notably, tPA directly acts against a specific thrombus, thereby dissolving cross-linked fibrin. Previous studies suggested that the administration of tPA did not worsen the prognosis or cause higher bleeding risks during concomitant thromboprophylaxis ( 27 , 28 ). To avoid adverse effect, such as reperfusion injury, electrolyte was monitored carefully every 4 h. Twelve hours after treatment, tPA was discontinued due to the possibility of reperfusion injury.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, tPA directly acts against a specific thrombus, thereby dissolving cross-linked fibrin. Previous studies suggested that the administration of tPA did not worsen the prognosis or cause higher bleeding risks during concomitant thromboprophylaxis ( 27 , 28 ). To avoid adverse effect, such as reperfusion injury, electrolyte was monitored carefully every 4 h. Twelve hours after treatment, tPA was discontinued due to the possibility of reperfusion injury.…”
Section: Discussionmentioning
confidence: 96%
“…Todavia, é de suma importância relatar que alguns fatores devem ser levados em consideração ao se estabelecer o prognóstico, como o acompanhamento clínico de felinos com acometimento de apenas um evento, uma vez que há relatos de recuperação no período de uma ou duas semanas, podendo levar até meses 18,20 . O felino encontra-se saudável, hígido e até a presente descrição deste trabalho, sem manifestar sinais compatíveis com novo evento tromboembólico 21,22 .…”
Section: Recima21 -Revista Científica Multidisciplinar Issn 2675-6218...unclassified
“…A etiologia mais comum, é a associação com a cardiomiopatia hipertrófica (CMH). Todavia, em menor proporção não é possível identificar causa subjacente (Guillaumin et al, 2022;Smith & Tobias, 2004).…”
Section: Introductionunclassified
“…O exame físico é útil para diagnosticar o FATE, baseando-se em cinco sinais cardinais: dor, paralisia/paresia, ausência de pulso arterial, palidez e resfriamento dos membros afetados (Cruz et al, 2022;Guillaumin et al, 2022;Quintana, 2013;Smith & Tobias, 2004).…”
Section: Introductionunclassified
See 1 more Smart Citation